PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA TEMA 6 SUBTEMA 3 PEMBELAJARAN 1 TENTANG PELESTARIAN MAKHLUK HIDUP DI KELAS IV SD GMIT BAUMATA - Maxsel Koro; Netty E. A. Nawa; Endang S. Benu (Journal of Character and ELementary Education, 2023)
This study aims to improve student learning outcomes in learning about theme 6, sub-theme 3 and learning-1 with the Project Based Learning model. This type of research is Classroom Action Research (CAR) with stages namely: Planning, Implementation, Observation and Reflection. This research took place at GMIT Baumata Elementary School, Kupang Regency, with the research subjects being all fourth grade students at GMIT Baumat Elementary School, Kupang Regency, totaling 14 people. The data collection techniques used by researchers in conducting research include observation techniques, test techniques, and documentation techniques. The results of this study indicate that the learning outcomes of students through the use of the Project Based Learning learning model have improved well. This can be proven by the achievement of the average learning completeness of class IV students, which totaled 14 people, namely in the first cycle the percentage of completeness was 71.43% (10 people who completed) and in the second cycle the percentage of completeness was 100% (14 people who completed). The increase in student learning outcomes is seen from the increase in the average score of evaluation test work. The other increase that occurred was in the activeness of students in the class which was assessed using the observation sheet that had been provided by the researcher. From the results of the research above, researchers can conclude that the use of Project Based Learning learning models can improve student learning outcomes.